Kritische Vernunft für demokratische Transformationen Festschrift für Christine Kulke - Geißel, Brigitte; Manske, Alexandra (Politikwissenschaft, 2008)
This book traces a scientific biography and thus reflects the development of gender-sensitive political science: its origins in Critical Theory with its visible connection to its paradigms, political science's preoccupation with work as the central 'crux' of gender-specific theory and politics, the discussion of political socialization as an obstacle and simultaneous starting point for women-specific emancipation, and finally globalization in its significance as an opportunity and danger for a gender-equitable democracy.This is why, for Christine Kulke, this commemorative volume also presents central themes of gender-specific political science: a commemorative volume and a kaleidoscope worth reading.